2011
DOI: 10.1044/1092-4388(2011/10-0029)
|View full text |Cite
|
Sign up to set email alerts
|

Differential Associations Between Sensory Response Patterns and Language, Social, and Communication Measures in Children With Autism or Other Developmental Disabilities

Abstract: Purpose Examine patterns of sensory responsiveness (i.e., hyperresponsiveness, hyporesponsiveness, and sensory seeking) as factors that may account for variability in social-communicative symptoms of autism and variability in language, social, and communication skill development in children with autism or other developmental disabilities. Method Children with autistic disorder (AD; n = 72, mean age = 52.3 months) and other developmental disabilities (DD; n = 44, mean age = 48.1 months) participated in a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
150
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 54 publications
(72 reference statements)
21
150
0
2
Order By: Relevance
“…Thus, in the studies by Rogers et al (2003) and Wiggins et al (2009), no relationship was found between the sensory symptoms and the ADOS social/communicative score, while this relationship was found in the study by Watson et al (2011). In this study, the children were older than in the other studies and, in addition to scales and questionnaires, behavioral evaluation measures were used to measure sensory processing, unlike in the aforementioned studies (except the one by Boyd et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 68%
“…Thus, in the studies by Rogers et al (2003) and Wiggins et al (2009), no relationship was found between the sensory symptoms and the ADOS social/communicative score, while this relationship was found in the study by Watson et al (2011). In this study, the children were older than in the other studies and, in addition to scales and questionnaires, behavioral evaluation measures were used to measure sensory processing, unlike in the aforementioned studies (except the one by Boyd et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 68%
“…In addition, children with ASD in our study were generally high-functioning, which prohibits us from generalizing our findings to more impaired individuals. Altered patterns of sensory behavior are reported to be more prevalent in low-functioning cases of ASD (Patten, Ausderau, Watson, & Baranek, 2013; Watson et al, 2011), potentially further limiting our power. Furthermore, the SERT promoter polymorphisms are, at best, an indirect assessment of SERT expression and function, hindering our ability to directly test the effects of SERT on sensory functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of sensory function in ASD have primarily focused on broad patterns of sensory behavior, which have been categorized as hyper- and hyporesponsiveness. While several reports indicate that hyporesponsiveness to sensory stimuli is highly prevalent in children with ASD and correlates strongly with clinical features (Foss-Feig, Heacock, & Cascio, 2012), it remains unclear whether patterns of hyperresponsive sensory behaviors are a distinctive ASD characteristic (Baranek, David, Poe, Stone, & Watson, 2006; Ben-Sasson et al, 2009; Rogers & Ozonoff, 2005; Tavassoli, Hoekstra, & Baron-Cohen, 2014; Watson et al, 2011). To clarify these findings, recent investigations of sensory processing have also analyzed patterns of behavior across multiple sensory modalities (Kern et al, 2006; Little et al, 2011; O’Riordan & Passetti, 2006; Tomchek & Dunn, 2007; L.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the most thorough meta-analysis to date found that sensory modulation issues consistently distinguish ASC and TD individuals across studies (Ben-Sasson et al, 2009). Sensory issues are largely separable not only from cognitive inflexibility (as argued above), but also from executive functioning (Boyd et al, 2009;Chen et al, 2009), and social interaction deficits (Watson et al, 2011), the latter observable as early as infancy (Baranek, 1999). Moreover, although the affected modalities can vary greatly between ASC individuals (perhaps explaining some of the ambivalence towards including sensory issues as a core symptom) there is some evidence that, within ASC individuals, severity of sensory modulation abnormalities highly correlates across sensory modalities (Kern et al, 2007).…”
Section: Two Additional Adi-r Factor Analyses Within the Restricted Amentioning
confidence: 98%